Pancasila sebagai Alat Pemersatu Bangsa Indonesia - Jelita Siahaan; Raras Agustina; Reodiva Jonandes; Riska Andi Fitriono (Fakultas Hukum, Universitas Diponegoro, 2022)
Indonesia is a country known for its diversity, 70% of Indonesia's total territory is water, making Indonesia's territory divided into 17,504 islands, 714 tribes, and has 1100 regional languages, this diversity has made Indonesia known as a rich country. This wealth certainly makes Indonesian citizens proud to be in this country, but with so much diversity there will also be many conflicts that will occur in Indonesia. Therefore, Pancasila is a unifying tool for the nation, meaning that Pancasila is a complete tool, to directly form the formulation of the goals and ideals of the Indonesian state, namely to realize social justice for all Indonesian people.